Refleksi Diri Mualaf Pasca Konversi Agama - Ahmad Ismail; Muhamad Farhan Abi Karami; Munsi Lampe (Refleksi: Jurnal Kajian Agama dan Filsafat, 2024)
This research seeks to comprehend the self-reflection undergone by those who have converted to Islam in Indonesia following their religious conversion. Religious conversion is a multifaceted social event, encompassing significant spiritual and social transformations for individuals. This study utilizes a descriptive qualitative methodology using a case study technique. Purposive sampling was employed to pick five informants who had converted to Islam within the year preceding the investigation, and one informant as a management of Mualaf Foundation. Data were gathered via comprehensive interviews to investigate the emotional, spiritual, and social experiences of converts following the recitation of the shahada. The study’s findings reveal that converts undergo a range of profound emotions throughout and following the conversion process, encompassing feelings of anxiety, skepticism, and finally serenity and a sense of proximity to Allah. Furthermore, converts have problems related to inadequate religious education and societal prejudice that impede their transition process. Self-reflection is a crucial instrument for converts to comprehend their transformations, establish new life objectives, and identify methods to engage with their communities. In conclusion, the post-conversion self-reflection process is intricate and demanding, however it offers converts the opportunity to enhance their spiritual comprehension and forge a new identity within Islam. This study emphasizes the need of augmented social support and religious instruction to aid converts in their spiritual development and social assimilation into wider groups.